2010
DOI: 10.1111/j.1399-3038.2010.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy knowledge, attitudes, and beliefs of parents with food-allergic children in the United States

Abstract: Parents of food-allergic children are responsible for risk assessment and management of their child's condition. Such practices are likely informed by parental knowledge, attitudes, and beliefs of food allergy. Our objective was to characterize food allergy knowledge and perceptions among parents with food-allergic children. Parents were recruited nationally between January 2008 and 2009 to complete the validated, web-based Chicago Food Allergy Research Survey for Parents of Children with Food Allergy. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 29 publications
2
69
0
3
Order By: Relevance
“…Food allergy is a common health issue in the school setting (43,44). Food-allergic children will be exposed to food ingestion when out of their parents' direct care and require proper management of the adrenaline administration.…”
Section: Schoolmentioning
confidence: 99%
“…Food allergy is a common health issue in the school setting (43,44). Food-allergic children will be exposed to food ingestion when out of their parents' direct care and require proper management of the adrenaline administration.…”
Section: Schoolmentioning
confidence: 99%
“…nosis, and management among patients and, potentially, physicians [12,13] . Patient-related causes could possibly be due to a tendency to interpret any food intolerance, even those with no immunological basis, as an "allergy."…”
Section: Discussionmentioning
confidence: 99%
“…Bollinger (2006) surveyed 87 families of children with food allergies and found that the majority of caregivers reported not only a significant impact of their child's food allergy on meal preparation, but also approximately half of caregivers reported that their child's food allergy significantly affected family social activities; 41% endorsed a significant impact of their child's food allergy on their own stress levels; 34% reported that the food allergy affected their child's school attendance; and 10% chose to home school their child because of their child's food allergy. Food allergies in children are also related to parental reports of strain on marriage and relationships, and almost half of parents of children with food allergies report experiencing hostility from other parents when attempting to accommodate their child's condition (Gupta et al, 2010). Parents report experiencing social isolation, frustration in their attempts to access resources needed to manage their child's food allergy symptoms, and feeling burdened by increased financial costs associated with their child's food allergy (McBride, McBride-Henry, & van Wissen, 2010).…”
Section: Parental Psychological Distress and Parenting Behaviorsmentioning
confidence: 99%